2012
DOI: 10.2169/internalmedicine.51.6671
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Safety of Donepezil in Elderly Patients with Alzheimer Disease

Abstract: Objective Donepezil is a widely used cholinesterase inhibitor for the treatment of Alzheimer's disease (AD), however its cholinergic adverse side effects on the cardiovascular system are still unclear. In this study, we aimed to examine the adverse side effects caused by donepezil on cardiac rhythm and postural blood pressure changes in elderly patients with Alzheimer Disease. Methods The ECG parameters including heart rate, PR, QT, QTc interval and QRS duration and postural blood pressure changes were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…It has also been described that acetylcholinesterase inhibitors may also induce cardiovascular side-effects although their effects on the cardiovascular system are still unclear. In this regard, it has been recently described that Donepezil, galantamine and rivastigmine are not associated with cardiovascular toxicity in elderly patients with AD [118]. …”
Section: Pharmacology Of Nachrsmentioning
confidence: 99%
“…It has also been described that acetylcholinesterase inhibitors may also induce cardiovascular side-effects although their effects on the cardiovascular system are still unclear. In this regard, it has been recently described that Donepezil, galantamine and rivastigmine are not associated with cardiovascular toxicity in elderly patients with AD [118]. …”
Section: Pharmacology Of Nachrsmentioning
confidence: 99%
“…Isik et al . directly compared the PR interval in a prospective study of 71 patients with Alzheimer's disease and reported no impact of donepezil hydrochloride on either heart rate or PR interval (Isik et al ., ). The study by Isik et al .…”
Section: Discussionmentioning
confidence: 97%
“…To date, various reports have been made of cases of atrioventricular block caused by donepezil hydrochloride (Suleyman et al ., ; Tanaka et al ., ), and we have also reported a case in which the administration of donepezil hydrochloride resulted in prolonged PR interval, and the additional administration of memantine further worsened the prolonged PR interval (Igeta et al ., ). Some reports, however, have suggested no clear prolongation of PR interval as a result of the administration of donepezil hydrochloride (Feldman et al ., ; Tariot et al ., ; Winblad et al ., ; Black et al ., ; Froelich et al ., ; Isik et al ., ), resulting in conflicting observations. Therefore, we implemented a study of the impact of donepezil hydrochloride administration on RR, PR, and QT intervals.…”
Section: Introductionmentioning
confidence: 99%
“…59,60 Several cases of syncope have been reported in patients who have been receiving donepezil treatment 50,57 ; 69% of these cases of syncope were associated with carotid sinus syndrome, sinus node dysfunction, complete atrioventricular block, paroxysmal atrial fibrillation, and severe orthostatic hypotension, whereas in 31% of the cases no cause of syncope was found. 57 Isik et al 61 performed an openlabel study involving 52 AD patients, a much larger study population as compared with previous works, [58][59][60] and found no changes in electrocardiogram or blood pressure, and concluded that the previous studies were confounded by comorbidities and medications. However, there is no clear evidence of the effect of donepezil on the cardiovascular autonomic system, and further randomized double-blind controlled studies are needed to assess the full extent of this effect.…”
Section: Side Effects and Drug Interactionsmentioning
confidence: 99%